Rekonstruksi Pengaturan Pemulihan Aset Berbasis Prinsip Beneficial Ownership untuk Mencegah Penyembunyian Kekayaan Ilegal - Febrian Rizky Akbar; Slamet Tri Wahyudi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Asset recovery is a strategic instrument in law enforcement against corruption and money laundering crimes. However, the practice of concealing illicit wealth through nominee schemes, shell companies, and offshore jurisdictions demonstrates weaknesses in national legal regulations, particularly regarding the identification of beneficial ownership. This study aims to analyze the weaknesses in Indonesia’s asset recovery regulations and to formulate a reconstruction of regulations based on the principle of beneficial ownership in order to prevent the concealment of illicit wealth. The research employs a normative juridical method with statutory, conceptual, and comparative law approaches. The results indicate that the existing regulations remain administrative in nature and have not yet been integrated into the asset recovery regime. Therefore, legal reconstruction is required through strengthening obligations for beneficial ownership disclosure, integrating cross-agency databases, and regulating non-conviction based asset forfeiture mechanisms. This study offers a more progressive regulatory model to enhance the effectiveness of asset recovery and close loopholes for concealing illicit wealth.